PENGARUH FAKTOR MAKRO EKONOMI DAN STRUKTUR MODAL TERHADAP RETURN SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA INDUSTRI BARANG KONSUMSI PERIODE 2019-2021 - Yolanda Fauzziyah; Arifin Siagian (Jurnal Satya Mandiri Manajemen dan Bisnis, 2024)
ABSTRACT This study aims to determine the effect of inflation, exchange rates, and capital structure on stock returns with profitability as an intervening variable in consumer goods sector companies on the Indonesia Stock Exchange (IDX), which publish financial reports from 2019-2021. This type of research is quantitative research. Population data is taken from consumer goods sector companies listed on the Indonesia Stock Exchange (IDX), which publish financial reports from 2019-2021. The sampling method used in this study was purposive sampling. From a population of 76 companies, there were 36 companies that met the sample criteria. So, the data sample in this study is 85. The analysis technique consists of multiple regression analysis and path analysis. The results of this study indicate that (1) Inflation has no effect on Profitability, (2) Exchange Rates have no effect on Profitability, (3) Capital Structure has an effect on Profitability, (4) Inflation has no effect on Stock Returns, (5) Exchange Rates have no effect on Stock Returns, (6) Capital Structure has an effect on Stock Returns, (7) Profitability has an effect on Stock Returns, (8) Inflation has an effect on stock returns through profitability, (9) Exchange rates has an effect on stock return through profitability, (10) Capital Structure has an effect on stock return through profitability. Keyword: Inflation, Exchange Rate, Capital Structure, Profitability, Stock Return